International Law and Global Politics in a Post-Pandemic World: Homo Sapiens? - Patrono, Mario (Victoria University of Wellington Law Review, 2022)
This article discusses the Coronavirus pandemic: A deep wound destined, sooner or later, to heal, or instead sow the seed of a global revolution? The first part examines the history of war and peace among nations to propose the idea of an International Court of Justice endowed with compulsory jurisdiction as the first step towards the creation of a world State. The second part further considers a changed New Global Order in the face of crises.